The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.0014-3820.2005.tb00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Correlates of Population Differentiation in Atlantic Herring

Abstract: The marine environment is characterized by few physical barriers, and pelagic fishes commonly show high migratory potential and low, albeit in some cases statistically significant, levels of genetic divergence in neutral genetic marker analyses. However, it is not clear whether low levels of differentiation reflect spatially separated populations experiencing gene flow or shallow population histories coupled with limited random genetic drift in large, demographically isolated populations undergoing independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,172 publications
(119 citation statements)
references
References 77 publications
12
107
0
Order By: Relevance
“…This was in contrast to the previous population genetic study of sole by Rolland et al (2007), which used only three nuclear EPIC markers. Our results are concordant with observations for several other marine Wsh species in the region, such as for turbot (Nielsen et al 2004), herring (André et al 2011;Bekkevold et al 2005), plaice (Hoarau et al 2002), hake (Lundy et al 1999), cod (Nielsen et al 2003) and sand goby (Larmuseau et al 2010a). The signiWcant diVerentiation between the North Sea and the Baltic transition zone is mainly attributed to geographic isolation, a bottleneck, selection on adaptive traits in Baltic populations or a combination thereof (Johannesson and André 2006;Larmuseau et al 2010b).…”
Section: Population Structuresupporting
confidence: 90%
“…This was in contrast to the previous population genetic study of sole by Rolland et al (2007), which used only three nuclear EPIC markers. Our results are concordant with observations for several other marine Wsh species in the region, such as for turbot (Nielsen et al 2004), herring (André et al 2011;Bekkevold et al 2005), plaice (Hoarau et al 2002), hake (Lundy et al 1999), cod (Nielsen et al 2003) and sand goby (Larmuseau et al 2010a). The signiWcant diVerentiation between the North Sea and the Baltic transition zone is mainly attributed to geographic isolation, a bottleneck, selection on adaptive traits in Baltic populations or a combination thereof (Johannesson and André 2006;Larmuseau et al 2010b).…”
Section: Population Structuresupporting
confidence: 90%
“…Nevertheless, numerically small but significant genetic differentiation has been detected in many marine pelagic fishes despite high dispersal capabilities and large effective population sizes [5,6,9,63]. In this study, multiple analyses showed that a weak but significant genetic structure existed in chub mackerel populations.…”
Section: Discussionmentioning
confidence: 60%
“…The biological peculiarities of these fishes combined with the apparent lack of physical barriers in the marine realm, are thought to facilitate extensive gene flow and low genetic differentiation among populations [1][2][3][4]. However, this long heldview was challenged by recent studies that cryptic population structuring has been increasingly detected in highly abundant and widely distributed migratory marine fishes [5][6][7][8][9]. The complicated interaction between marine environment and biological characteristics of marine fishes could sufficiently account for the differentiation processing.…”
Section: Introductionmentioning
confidence: 99%
“…As in walleye, natal site fidelity appears to maintain reproductive isolation in a number of species, including rainbow smelt (Osmerus mordax; Bernatchez 1997), Atlantic herring (Clupea harengus; Bekkevold et al 2005;Jorgensen et al 2005), walleye pollock (Theragra chalcogramma; O' Reilly et al 2004), and mackerels (Scomber spp. ; Zardoya et al 2004).…”
Section: Correspondence Of Patterns In Walleye With Other Fishesmentioning
confidence: 99%